2020
DOI: 10.1007/s10067-020-05408-6
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of an adapted core strength endurance test battery in individuals with axial spondylarthritis

Abstract: Objectives To adapt the core strength endurance test battery (aCSE), previously used for testing athletes, to a target group of patients with axial spondylarthritis (axSpA), to evaluate its intra-tester reliability and its associations with disease-specific factors. Methods A cross-sectional study was conducted at axSpA exercise therapy groups, including both axSpA patients and the physiotherapist group leaders (PTs). The aCSE was used to measure the isometric strength endurance of the ventral, lateral, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
1
0
2
Order By: Relevance
“…Die Zeitaufzeichnung wird gestoppt, wenn die Versuchsperson zum dritten Mal den Kontakt mit dem Stab verliert. Es wurde die detaillierte Instruktion zur Durchführung der modifizierten Rumpfkrafttestbatterie beschrieben und die Intertester-Reliabilität untersucht [12].…”
Section: Modifizierter Rumpfkrafttestunclassified
See 1 more Smart Citation
“…Die Zeitaufzeichnung wird gestoppt, wenn die Versuchsperson zum dritten Mal den Kontakt mit dem Stab verliert. Es wurde die detaillierte Instruktion zur Durchführung der modifizierten Rumpfkrafttestbatterie beschrieben und die Intertester-Reliabilität untersucht [12].…”
Section: Modifizierter Rumpfkrafttestunclassified
“…Das Auswahlprozedere erfolgte im Rahmen von Masterarbeiten an der ZHAW. Aufgrund dieser Kriterien wurden für die Evaluation der kardiorespiratorischen Fitness der Chester Step Test (CST) [11], für die Kraft die modifizierte Rumpfkrafttestbatterie [12], für die Beweglichkeit der Bath Ankylosing Spondylitis Metrology Index (BASMI) [13] und für die Neuromotorik der Einbeinstand (Single Leg Stance Test, SLST) [14] ausgewählt.…”
Section: Introductionunclassified
“…Good isometric muscular endurance has been understood to prevent LBP occurrence ( Biering-Sørensen, 1984 ). However, a recent study by Rausch et al (2021) reported no correlations between endurance tests that assess an isometric strength of the dorsal, lateral and ventral chains of the core muscles and perceived strength performance, functional status, and self-reported disease-specific pain in individuals with axial spondylarthritis. Furthermore, similar scores in the Bunkie test (a functional performance test consisting of 5 test positions performed bilaterally) were found in subjects with and without a prior history of musculoskeletal injury ( Brumitt, 2015 ).…”
Section: Introductionmentioning
confidence: 97%